PERBANYAKAN TANAMAN KRISAN (Chrysanthemum morifolium) MELALUI KULTUR JARINGAN - Ita Dwimahyani; S Gandanegara (BERITA BIOLOGI, 2001)
Vegetatively propagated Chrysanthemum morifolium has been carried out by tissue culture.Explants derived from shoot-tip of three chrysant genotypes were used for the experiment. Shoot-tips taken from terminal branch and sterilized with 0.05% HgCb for 30 minutes and rinsed with distilled water three times.Shoot-tips were cultured on MS regeneration medium containing 1 mg/1 BAP and 0.02 mg/1 NAA.Shoot regeneration occurred 20 days after cultured.A number of tiny shoots were then transferred to fresh regeneration medium for 3 weeks and regenerated shoots were calculated.Results showed that plant genotypes had different response into plant regeneration. Genotype Ku-Ch had better response compared to other two genotypes which shown from number of plantlets produced by this genotype on the third sub-culture.